Quality monitoring during installation of large tempered glass structures - Yatsyk, Vasyl; Kurylyak, Nazar (Видавництво Львівської політехніки, 2023)
The need to ensure the quality of installation of large-sized structures made of tempered glass following European standards is emphasized, the relevance of which is emphasized with the acquisition of the status of a candidate for the EU by our country. This provides access to the construction industry to European manufacturers and exports the products of Ukrainian enterprises abroad. Unification of requirements for both fitting tools and quality control tools during the deployment and operation of large-sized tempered glass products has been ensured. The need to automate measuring operations from the moment of manufacturing tempered glass to the moment of its putting in place at the construction site is substantiated. It is shown that for the automation of measuring operations during the insertion of large-sized panes of tempered glass, it is appropriate to use optical measurement methods.
Keywords: quality monitoring; large-scale constructions; standards; harmonization; tempered glass